Internet‐based psychological therapies: A qualitative study of National Health Service commissioners and managers views. (31st March 2021) - Simon, Natalie; Ploszajski, Matt; Lewis, Catrin; Smallman, Kim; Roberts, Neil P.; Kitchiner, Neil J.; Brookes‐Howell, Lucy; Bisson, Jonathan I.
Abstract : Objectives: To explore in‐depth the views on Internet‐based psychological therapies and their implementation from the perspective of National Health Service (NHS) commissioners and managers. Design: Qualitative interview study. Method: Ten NHS commissioners and managers participated in a semi‐structured, co‐produced interview. Each transcribed interview was double‐coded and thematically analysed using The Framework Method. Results: Interviews generated three main themes. (1) Capacity issues across psychological therapy services create barriers to face‐to‐face therapies, and Internet‐based interventions offer a solution. (2) Despite reservations, there is growing acceptance of Internet‐based therapies. Different ways of connecting with patients are required, and Internet‐based treatments are accessible and empowering treatment options, with guided self‐help (GSH) preferred. Internet‐based interventions may however exclude some individuals and be a threat to the therapeutic relationship between patient and practitioner. (3) Successful roll‐out of Internet‐based interventions would be facilitated by a strong empirical‐ or practice‐based evidence, a national coordinated approach and timely training and supervision. Barriers to the roll‐out include digital intervention set‐up costs and delays due to NHS inflexibility. Conclusions: The study highlights factors influencing access to Internet‐based therapies, important given the rapid evolution of e‐therapies, and particularly timely given increasing use of remote therapies due to COVID‐19 restrictions. Interviewees were open to Internet‐based approaches, particularly GSH interventions, so long as they do not compromise on therapy quality. Interviewees acknowledged implementation may be challenging, and recommendations were offered. Practitioner points: There is a shift in practice and increasingly positive views from NHS staff around remote psychological therapies and different ways of connecting with patients, particularly since the COVID‐19 pandemic. There is a strong preference for Internet‐based psychological interventions that are guided and that include built‐in outcome measures co‐produced with service users. There is a need to raise awareness of the growing evidence base for Internet‐based psychological therapies, including research examining therapeutic alliance across Internet‐based and face‐to‐face therapies. Challenges implementing Internet‐based psychological therapies include therapist resistance to changing working practices in general, and inflexibility of the NHS, and national, coordinated implementation efforts are encouraged.